Determination of the Calibration Equation for FBG Temperature Sensors - Moldovan, Ovidiu Gheorghe; Moldovan, Alin Octavian; Tarca, Radu Catalin; Craciun, Dan (Recent Innovations in Mechatronics, 2021)
This paper presents a brief introduction to FBG sensor technology and its applications. Then the procedure for determining the sensor calibration equations is presented. These equations are determined for each individual sensor and are necessary to perform the trans-oceanographic measurement of the FBG sensor’s wavelength variation in the measured parameter.